EVALUASI REDESIGN WEBSITE BERBASIS FIGMA TERHADAP KEPUASAN PENGGUNA(STUDI KASUS PADA BBPMP JAWA TENGAH) - Nadiva Andreabella Shazita; Irdha Yunianto; Muhammad Sholikhan (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
This study aims to evaluate the Figma-based redesign of the BBPMP Central Java website to enhance user satisfaction and visual consistency with national graphic standards. Using a qualitative descriptive approach and the Research and Development (R&D) method, the process included needs analysis, prototype design, expert validation, and user testing. Data were collected through observation, interviews, and Likert-scale questionnaires. The results show that a user-centered redesign significantly improves navigation, visual appeal, and user satisfaction with the website interface. Figma proved to be an effective collaborative tool for developing interactive and standardized design prototypes. These findings provide strategic insights for educational institutions to enhance the quality and attractiveness of digital platforms.